2010
DOI: 10.1007/s00535-010-0278-5
|View full text |Cite
|
Sign up to set email alerts
|

AFP, AFP-L3, DCP, and GP73 as markers for monitoring treatment response and recurrence and as surrogate markers of clinicopathological variables of HCC

Abstract: DCP is a more effective tumor marker than AFP and AFP-L3. AFP-L3 showed comparable accuracy to AFP but no benefit was found in their combination. GP73 did not play a significant role in this context. Indices of tumor invasiveness were most closely associated with DCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 38 publications
6
123
0
2
Order By: Relevance
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, in addition to AFP, new biomarkers possessing fucosides have been discovered. For example, Golgi protein 73 (GP73) content in the blood of patients with HCC was found to be elevated, and the protein was ␣1-6-hyperfucosylated (43)(44)(45)(46). In addition, patients with liver cirrhosis and liver cancer had increased levels of triantennary glycan containing outer arm (␣1-3)-fucosylation in ␣-antitrypsin in the blood, but increases in core (␣1-6)-fucosylation were observed only on ␣1-antitrypsin from patients with liver cancer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tatarinov and Abelev 4 first used AFP as a diagnostic marker for HCC in 1964, and the mounting clinical evidence since this report indicates that AFP elevation is linked to a more aggressive tumor phenotype characterized by vascular invasion, metastasis and poor differentiation. 5 However, the diagnostic accuracy of AFP is often questionable because of its low sensitivity; it remains to be determined whether AFP levels in HCC represent anything more than a coincidental epiphenomenon.…”
Section: H Epatocellular Carcinoma (Hcc) Ismentioning
confidence: 99%